Application of response surface methodology for protein enrichment of cassava peel as animal feed by the white-rot fungus Panus tigrinus M609RQY - Ruqayyah, T.I.D.; Jamal, Parveen; Alam, Md Zahangir; Mirghani, Mohamed Elwathig Saeed; Jaswir, Irwandi; Ramli, Nazaruddin (Elsevier Inc., 2014)
Response surface methodology (RSM) was employed to optimize the process conditions for production of protein-enriched animal feed from cassava peel by a locally isolated white rot fungus Panus tigrinus. Face-Centered Central Composite Design (FCCCD) with three variables (pH, inoculum size and moisture content) was used to determine the effect of these operational parameters on the protein increase of cassava peel as animal feed under solid-state fermentation. A significant quadratic model was obtained for protein increase using this design. Results of the statistical analysis showed that a significant (P < 0.05) linear effect was obtained for moisture content, while only the interaction effect between moisture content and inoculum size was significant (P < 0.01). The optimum process combination was found to be 75% (v/w) of moisture content, a pH of 5.3 and 7% (v/w) inoculum size. A maximum increase of protein (55.16%) was obtained during 15-day of solid-state fermentation